The Cow in the Room Livestock and Climate Engagement at the 2022 United Nations Climate Change Conference (COP27) - Mugo, Cynthia; Victor, Michael; Flintan, Fiona E. (International Livestock Research Institute, 2022)
The UN Framework Convention on Climate Change Conference (UNFCCC COP27) was held November 6-18, 2022, in Sharm el Sheikh, Egypt, and ILRI was there actively telling the livestock sustainability story. Too often, climate discussions focus on the negative aspects of intensive livestock production. The livestock sector is often cited as the most intensive emitter of greenhouse gases within agricultural production systems, contributing to about 18% of anthropogenic greenhouse gas emissions, mainly from methane and nitrous oxide. However, science shows that sustainable livestock can bring adaptation, mitigation and economic growth benefits to both people and the planet. In addition, sustainable livestock production, especially in developing countries, can contribute to building climate resilience while boosting low-emission development and supporting food security and livelihoods. With food, for the first time, taking centre stage at COP27, the CGIAR Research Initiative on Livestock Climate and Systems Resilience, ILRI and the GLAD Project, along with partners, sought to ensure sustainable livestock is recognised as essential to climate change mitigation. As part of this process, we designed an integrated engagement, communications and media outreach plan. This included the innovative campaign dubbed ‘cow in the room’ #LetsTalkLivestock to drive our participation and narrative to COP27 and beyond.